2010
DOI: 10.1002/jid.1686
|View full text |Cite
|
Sign up to set email alerts
|

Trust and ROSCA membership in rural Cameroon

Abstract: A key element of Rotating Saving and Credit Associations (ROSCAs) is the trust which members must place in each other, and which replaces formal financial contracts in places where financial transactions costs are high. However, there is very little evidence on the relationship between trust and ROSCA membership. We address this issue using new experimental data from rural Cameroon. We find large and statistically significant differences between trust among ROSCA members and trust among other people. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…A key element of this design is that each participant knows that he/she is randomly matched with a member of his/her own community but he has no idea of his/her opponent's identity. On average, first movers send 53 percent of their endowment, which is consistent with the results in Castillo and Carter (2003) for South Africa and substantially lower than the amount shared in Etang et al (2010). With this design of the trust game that we call Community Condition of Trust Game (CCT), we expect to capture the level of trust (the amount sent by the first player called the CCT trust) which is required for subjects to participate in collective activities.…”
Section: The Trust Gamesupporting
confidence: 80%
“…A key element of this design is that each participant knows that he/she is randomly matched with a member of his/her own community but he has no idea of his/her opponent's identity. On average, first movers send 53 percent of their endowment, which is consistent with the results in Castillo and Carter (2003) for South Africa and substantially lower than the amount shared in Etang et al (2010). With this design of the trust game that we call Community Condition of Trust Game (CCT), we expect to capture the level of trust (the amount sent by the first player called the CCT trust) which is required for subjects to participate in collective activities.…”
Section: The Trust Gamesupporting
confidence: 80%
“…This result is consistent with Schechter () who also finds a negative relationship between education and amount sent in Paraguay. However, Etang et al () find a significant positive effect between education and amount sent in Cameroon.…”
Section: Resultsmentioning
confidence: 95%
“…To our knowledge, two studies have been conducted focusing on the correlation between trust and group membership in a developing country setting. Etang et al, () find that members of rotating savings and credit associations were more trusting than non‐rotating savings and credit association members. In contrast, Karlan () finds evidence that participants in a microfinance intervention, FINCA in Peru, were not more trusting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust is high as members know each other (Laffont and N'Guessan, 2000). However, in an experimental study in a village in Cameroon, where half the adult population was in some ROSCA, it was found that ROSCA members did not necessarily have kinship or friendship ties with other members (Etang et al ., 2011). Chiteji (2002) examined the ROSCA's ability to enforce its terms of membership and the connection between enforcement costs and the desirability of ROSCA formation.…”
Section: Other Governance Modelsmentioning
confidence: 99%